Research on the Management Strategy of Expressway Traffic Safety Facilities Engineering - Wang, Xiaoyi (Journal of Theory and Practice of Management Science, 2023)
Improving the advanced highway transportation system fully demonstrates China's strong strength. The purpose of this article is to comprehensively discuss the basic types and functions of highways, and to provide a detailed discussion on them, in order to provide a meager contribution to the reasonable planning and construction of highways in China that meet the national conditions.